AN ANALYSIS OF FOURTH SEMESTER STUDENTS’ ERRORS IN USING GERUND - Widiadnya, I Gusti Ngurah Bagus Yoga (IKIP SARASWATI TABANAN, 2025)
ABSTRACT This research aims to identifythe errors in using gerund who committed by the students, as: the percentage of errors used the theory of Bluman (2009:74), the types of error used the theory of Dulay, Burt, & Krashen, (1982:146-191), and the sources of error used the theory of Richards (1971) as cited in Ellis (1994). The subject of this research was the students at the fourth semester of English Education Study Program, Faculty of Language and Arts Education, IKIP Saraswati in Tabanan. In this research qualitative was the method in analyzing and describing the data, then used random sampling technique in taking the samples, and some techniques also were delivered in order to get the data, as: English test, used gerund as the instrument in testing the students’ ability, as: subject of a sentence, object of a preposition, after a possessive, and gerund used after the certain verbs.The result of this research has found the types of errorr: misformation, addition, and omission.